The Arcminute Microkelvin Imager - Zwart, J.; Barker, R.; Biddulph, P.; Bly, D.; Boysen, R.; Brown, A.; Clementson, C.; Crofts, M.; Culverhouse, T.; Czeres, J.; Dace, R.; Davies, M.; et al. (Oxford University Press, 2008)
The Arcminute Microkelvin Imager is a pair of interferometer arrays operating with sixfrequency channels spanning 13.9–18.2 GHz, for observations on angular scales of 30 arcsec–10 arcmin and for declinations greater than -15?; the Small Array has a sensitivity of30 mJy s-1/2 and the Large Array has a sensitivity of 3mJy s-1/2. The telescope is aimedprincipally at Sunyaev–Zel’dovich imaging of clusters of galaxies. We discuss the design ofthe telescope and describe and explain its electronic and mechanical systems.